Sustainable human capital development through entrepreneurial education - Ahmad Anwar Mohamed Ismail; Aweng Eh Rak; Ibrahim Che Omar (2011)
With the increasing concern a decade ago on job competition and employment opportunities for graduates of local universities in the country, the Malaysian Ministry of Higher Education have rightly embark on a policy requiring all institutions of higher education embed in their teaching curricula elements of entrepreneurial education. Universities are seen as the training ground for producing and shaping the minds of future generations. Institutions of higher education also provide an important intellectual environment and create the social setting for students to interact, exchange and propound ideas not only for specific courses they have chosen to pursue but should also have a good mix with courses that contain commercial and entrepreneurial elements. Universities are expected and must play an additional role, over and above the mundane traditional research and teaching, by embedding into the curriculum entrepreneurial elements in their educational programmes. Entrepreneurial exposure and training should start right at the beginning as the students step into the university and the onus is on the higher education authorities to address the need for producing competent and techno-savvy graduates who are equally competent in entrepreneurial skills. Not only must graduates be conversant with these skills but they should also be imbued with the right attitude in handling as well as tackling community issues right at the grass root levels and hence community service programmes are part and parcel of this learning.But the question remained whether entrepreneurship education already intoduced would be able to develop human capital sustainably as each institutional has its own way of addressing and implementing this. An effective entrepreneurship education has to be formulated and the delivery system has to be standardized. There has been a perceptible shift in teaching and learning over the last decade towards this objective but in order to ensure the current practice meet the primary goal of eventually producing sustainable human capital with entrepreneurial attributes future curiculum in education should leverage on appropriate programmes and delivery system being drawn up to suit the new learning environment. Above all. the existing crop of educators, and the new ones recruited, ought to be transformed over a series of training and industry exposures from being ordinary teachers to one of entrepreneurial educators. Good programmes and delivery systems with sufficient numbers of entrepreneurial educators is not the panacea for the success of entrepreneurship education if the management and leadership itself is not entrepreneurial enough. This paper highlights the important elements of entrepreneurship education for sustainable human capital development in higher education in Malaysia with some programmes already implemented in Universities Malaysia Kelantan